Secure the soul: Christian piety and gang prevention in Guatemala - O'Neill, Kevin Lewis (University of California Press, 2015)
"Secure the Soul shuttles between the life of Mateo, a born-again ex-gang member in Guatemala and the gang prevention programs that work so hard to keep him alive. Along the way, this poignantly written ethnography uncovers the Christian underpinnings of Central American security. In the streets of Guatemala City--amid angry lynch mobs, overcrowded prisons, and paramilitary death squads--millions of dollars empower church missions, faith-based programs, and seemingly secular security projects to prevent gang violence through the practice of Christian piety. With Guatemala increasingly defined by both God and gangs, Secure the Soul details an emerging strategy of geopolitical significance: regional security by way of good Christian living"--Provided by publisher